The Impact of Social Mobilization on Health Service Delivery and Health Outcomes : Evidence from Rural Pakistan - Gine, Xavier; Khalid, Salma; Mansuri, Ghazala (World Bank, Washington, DC, 2018)
This paper uses a randomized community development program in rural Pakistan to assess the impact of citizen engagement on the quality of public health services. The program had a strong emphasis on organizing women, who also identified health services as a development priority at baseline. Assessing the program at midline, the paper finds that the mobilization effort alone had a significant impact on the performance of village-based health providers. The study detects economically large improvements in pregnancy and well-baby visits by lady health workers, as well as increased utilization of pre- and post-natal care by pregnant women. In contrast, the quality of supra-village health services did not improve, underscoring the importance of community enforcement and monitoring capacity for improving service delivery.